Unveiling the effects of heteroatom (Cl, S, N) doping on chronoamperometrically synthesized graphene oxides and their interaction with glyme-based electrolytes in sodium-ion batteries - Almarzoge, MohammedMustafa; Gencten, Metin; Ozsin, Gamzenur (ELSEVIER, 2026)
Na-ion batteries (SIBs) are promising energy storage devices, with graphene derivatives emerging as new anode materials. Chronoamperometry enables precise, mild synthesis of high-quality graphene oxide. Here, chlorine-, sulfur-, and nitrogen-doped graphene oxides (ClGO, SGO, NGO) are fabricated via a simple, straightforward, cost-effective, and ambient-condition method that does not require an inert atmosphere chronoamperometric method and tested as SIB anodes in an ether-based electrolyte. The utilization of diglyme as an electrolyte solvent improved the overall capacity and cycle life of DGO anodes, as diglyme is considered a co-intercalating electrolyte that contributes to the storage of Na+. Morphological analyses reveal that all powders exhibit a two-dimensional structure with uniformly dispersed dopant atoms. The single DGO electrodes show initial discharge capacities of similar to 415, 733, and 952 mAh g(-1) at 0.1C for ClGO, SGO, and NGO, respectively. Electrochemical tests demonstrate that ClGO, SGO, and NGO electrodes deliver reversible capacities of similar to 78, 199, and 240 mAh g(-1) after 500 cycles at 2C (200 mA g(-1)). After 100 cycles at 5C (1000 mA g(-1)), they retain similar to 90, 96, and 78 mAh g(-1), showing high stability. At 10C, reversible capacities of similar to 125, 210, and 260 mAh g(-1) are sustained after 50 cycles. All DGO samples exhibit a mixed charge storage mechanism, primarily governed by capacitive control, with a minor contribution from diffusion-controlled processes, signifying rapid charge transfer and effective ion storage characteristics. These results highlight a simple chronoamperometric route to produce DGO anodes with excellent stability and capacity, providing a promising pathway for large-scale SIBs applications.
Keywords: Sodium-ion batteries; Graphene oxide; Doped graphene; Chronoamperometric method; Electrochemical performance; Ether based electrolyte; NITROGEN-DOPED GRAPHENE; ANODE MATERIALS; RAMAN-SPECTROSCOPY; LITHIUM-ION; CARBON; PERFORMANCE; GRAPHITE; STORAGE; XPS; TEMPERATURE; Chemistry; Materials Science